AN ANALYSIS OF SEVENTH GRADE STUDENTS ABILITY IN WRITING PROCEDURE TEXT AT SMPN 2 KOTA SERANG: Analisis Kemampuan Menulis Teks Prosedur Siswa Kelas Tujuh di SMPN 2 Kota Serang - Deprilya, Aisyah; Aira Juniar Mutiara Halim; Ika Handayani; Diyah Setyorini; Mentari Viona (Universitas Aisyah Pringsewu, 2025)
This study examines the ability of seventh-grade students at SMPN 2 Kota Serang to write procedure texts. Using a quantitative descriptive method, data were collected from a sample of 35 students through a written test where students created their own procedure texts. The findings revealed that 51.43% of students achieved